BAG3 Protein Is Involved in Endothelial Cell Response to Phenethyl Isothiocyanate. (31st May 2018) - Franceschelli, Silvia; Bruno, Anna Paola; Festa, Michela; Falco, Antonia; Gionti, Elisa; d'Avenia, Morena; De Marco, Margot; Basile, Anna; Iorio, Vittoria; Marzullo, Liberato; Rosati, Alessandra; Pascale, Maria
Abstract : Phenethyl isothiocyanate (PEITC), a cruciferous vegetable-derived compound, is a versatile cancer chemopreventive agent that displays the ability to inhibit tumor growth during initiation, promotion, and progression phases in several animal models of carcinogenesis. In this report, we dissect the cellular events induced by noncytotoxic concentrations of PEITC in human umbilical vein endothelial cells (HUVECs). In the early phase, PEITC treatment elicited cells' morphological changes that comprise reduction in cell volume and modification of actin organization concomitantly with a rapid activation of the PI3K/Akt pathway. Downstream to PI3K, PEITC also induces the activity of Rac1 and activation of c-Jun N-terminal kinase (JNK), well-known regulators of actin cytoskeleton dynamics. Interestingly, PEITC modifications of the actin cytoskeleton were abrogated by pretreatment with JNK inhibitor, SP600125. JNK signaling led also to the activation of the c-Jun transcription factor, which is involved in the upregulation of several genes; among them is the BAG3 protein. This protein, a member of the BAG family of heat shock protein (Hsp) 70 cochaperones, is able to sustain survival in different tumor cell lines and neoangiogenesis by directly regulating the endothelial cell cycle. Furthermore, BAG3 is involved in maintaining actin folding. Our findings indicate that BAG3 protein expression is induced in endothelial cells upon exposure to a noncytotoxic concentration of PEITC and its expression is requested for the recovery of normal cell size and morphology after the stressful stimuli. This assigns an additional role for BAG3 protein in the endothelial cells after a stress event.